Current problems of learning foreign language by advanced academic staff - Tsaryova A. V. (Interactive science, 2019)
the article is devoted to the current problems of learning foreign language by advanced academic staff. The author outlines that academic staff learn a foreign language to upgrade their skills, therefore while teaching advanced adults it is necessary to take into consideration some peculiarities which are connected to their life and educational experience. The main advantage is in immediate application of acquired skills and knowledge. The author comes to the conclusion that, upgrading his or her skills by learning foreign language an academic becomes the unique specialist who implements innovative methods and projects.
Keywords: иностранный язык; повышение квалификации; самообразование; письменная речь; foreign language; advanced level; communicative approach; self-education; writing; продвинутый уровень; научно-преподавательский состав; коммуникативная направленность обучения; academic staff; upgrade of skills